Effect of the Implementation of a New Electronic Health Record System on Surgical Case Turnover Time. - McDowell, Joseph; Wu, Albert; Ehrenfeld, Jesse; Urman, Richard (Journal of Medical Systems, 2017)
Many health care providers, hospitals, and hospital systems have adopted new electronic health records (EHR) to streamline patient care and comply with government mandates. Commercial EHR vendors advertise improved efficiency, but few studies have been performed to validate these claims. Therefore, this study was performed to evaluate the effect of deploying a new EHR system on operating room efficiency and surgical case turnover time (TOT) at our institution. Data on TOT were collected after implementation of a new EHR (Epic) from June 2015 to May 2016, which replaced a legacy system of both paper and electronic records. These TOTs were compared to data from the same months in the preceding year. Mean TOT and standard deviations were calculated. The two-sample t-test was used to compare means by month and the F-test was used to compare standard deviations. There was a significant increase in TOT (63.0 vs. 53.0 min, p < 0.001) in the first month after implementation. This improved by the second month (59.0 vs. 53.0 min, p < 0.001), but the relative increase persisted until the end of the fifth month after which it remained around the pre-implementation baseline until the end of the study. The standard deviation significantly decreased after the fourth month post-implementation and persisted throughout the studied period. We found that implementation of an EHR led to a significant decrease in efficiency that persisted for five months. While EHRs have the potential to improve hospital workflow, caution is advised in the case of operating room implementation. While the mean TOT did not improve beyond the pre-implementation baseline, the standard deviation was significantly improved after the first four months.